Determinants of users’ continuance intention toward digital innovations: Are late adopters different? - Jahanmir, Sara F. (2022)
This study examines the users of digital innovations with covariance-based structural equation modeling (CBSEM) and a fuzzy-set qualitative comparative analysis (fsQCA) to understand the factors that drive their continuance intention. We examine the interplay between the perceptual factors related to the user experience with a digital product and personal factors that characterize late adoption. The findings highlight that perceived radicalness is a core condition to achieve the users’ continuance intention in a digital context. The findings contribute to theory by providing a better understanding of how personal factors in adoption interact with other determinants of the continuance intention. The study also presents practical implications. The results show that in the case of late adopters, firms should invest in both the radicalness and high system quality of their digital innovations.